ANALISIS KUALITATIF BISNIS ASURANSI MIKRO DI INDONESIA - Mulawarman Awaloedin ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
The purpose of this research is to explain the phenomenon occured in micro Insurance industry in Indonesia after the launch of the grand design of the Indonesian micro Insurance development. Having used a case study method, the researcher conducted some interviews with a number of  practitioners, and obtained some  information that micro insurance is still unable to develop if seen from the total population of the people in Indonesia. Micro insurance products are still scattered in big cities, and they have not touched the lower income people if refered to the basic concept of micro insurance. This needs a breakthrough in order to develop the micro insurance, as in the case with our neighbor country, the Philipines, which  is more advanced in developing this insurance scheme. In order to develop this micro insurance business, it is necessary to develop it through a network of small communities, which are found mostly in the lower middle class. Beside that, marketers also need  to be equiped with a set of tools, such as an adequate ICT -based market (community) database. Therefore, a micro insurance businesses to be developed needs to be adjusted to the conditions of the Indonesian state, for example in the case of micro insurance, for agriculture, livestock, fishermen, especially for rural areas. Meanwhile, for urban areas, micro insurance businesses that are attractive are personal accidents, property, and motor and vehicles.